2021
DOI: 10.3390/app112211042
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Eating Habits and Perceived Benefits of Physical Activity and Body Attractiveness among Adolescents from Northeastern Romania

Abstract: The purpose of this paper was to present the results of the evaluation of 1320 adolescents from 4 high schools in Iaşi, Romania regarding their eating habits and perceived benefits of physical activity and body attractiveness after they completed an anonymous questionnaire. The data analysis was performed using IBM SPSS version 18. The analysis of the nutritional status showed that over 70% of adolescents were of a normal weight. Most of them (63.56%) consumed 3–4 meals/day, with breakfast being the most skipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…A study revealed high physical activity in adolescent boys, nutrition awareness in girls, and a strong link between self-perceived body attractiveness and weight status. It also highlighted the need for school-based nutrition education [56]. Another study found that pandemic-induced telework led to increased screen time, decreased physical activity, weight gain, and poor sleep quality (less than 6 h on some weeknights) among young computer workers [57].…”
Section: Physical Activitymentioning
confidence: 99%
“…A study revealed high physical activity in adolescent boys, nutrition awareness in girls, and a strong link between self-perceived body attractiveness and weight status. It also highlighted the need for school-based nutrition education [56]. Another study found that pandemic-induced telework led to increased screen time, decreased physical activity, weight gain, and poor sleep quality (less than 6 h on some weeknights) among young computer workers [57].…”
Section: Physical Activitymentioning
confidence: 99%
“…A controlled trial of dietitian-led improvements in the dietary quality of patients with anxiety disorders showed that dietary nutrition significantly improved patients' symptoms (Forsyth et al, 2015). However, some students with less self-control may overeat, increasing the risk of overweight or obesity (Anton-Păduraru et al, 2021). In addition, dietary nutrition has been used to regulate dietary quality to play an important moderating role between sleep and mental health (Zhao et al, 2021).…”
Section: The Mediating Role Of Dietary Nutritionmentioning
confidence: 99%
“…can effectively control and improve the physique, BMI, cortical thickness and hip circumference of obese adolescents ( 9 , 10 ). The compound intervention of healthy eating habits and sports education program can significantly reduce the incidence of BMI and obesity in 62% of school children ( 11 ). The health promotion exercise program has significant positive effects on improving the risk factors (triglycerides, total cholesterol, glycosylated hemoglobin, etc.)…”
Section: Introductionmentioning
confidence: 99%